A Review of Green Synthesis of Metal Nanoparticles Using Algae - Mukherjee, Abhishek; Sarkar, Dhruba; Sasmal, Soumya (Frontiers in Microbiology, 2021)
The ability of algae to accumulate metals and reduce metal ions make them the superior contender for the biosynthesis of nanoparticles and hence they are called bio-nano factories as both the live and dead dried biomass are used for the synthesis of metallic nanoparticles. Microalgae, forming a substantial part of the planet's biodiversity, are usually single-celled colony-forming or filamentous photosynthetic microorganisms, including several legal divisions like Chlorophyta, Charophyta, Bacillariophyta. Whole cells of Plectonema boryanum (filamentous cyanobacteria) proved efficient in promoting the production of Au , Ag and Pt nanoparticles. The cyanobacterial strain of Anabaena flos-aquae, Calothrix pulvinate were used to implement the biosynthesis of Au, Ag, Pt nanoparticles. Once synthesized within the cells, the nanoparticles were released into the culture media where they formed stable colloids easing their recovery. Lyngbya majuscule and Chlorella vulgaris have been reported to be used as a cost-effective method for Ag nanoparticles synthesis. Dried edible algae (Spirulina platensis ) was reported to be used for the extracellular synthesis of Au, Ag and Au/Ag bimetallic nanoparticles. Synthesis of extracellular metal bio nanoparticles using Sargassum wightii and Kappaphycus alvarezi have also been reported.Bioreduction of Au (III)- Au (0) using the biomass of brown alga, Fucus vesiculosus and biosynthesis of Au nanoparticles using red algal (Chondrus crispus ) and green algal (Spyrogira insignis) biomass have also been reported.